Statistical characterization of nucleic acid sequence functional domains. - Smith, T F (1983)
It has long been recognized that various genome classes were distinguishable on the basis of base composition and nearest neighbor frequencies. In addition Grantham et al. (8) have recently presented evidence that these distinctions are preserved at the level of codon usage. As discussed in this report it is now clear that these and related statistics can uniquely characterize the various functional domains of the genome. In particular peptide coding, intervening segments, structural RNA coding and mitochondrial domains of the vertebrate genome are uniquely characterizable. The statistical measures not only reflect understood functional differences among these domains but suggest others. The ability of these simple statistics of nucleic acid sequences to reflect so much of the encoded complex pattern information and/or effects of selective constraints is somewhat surprising. Here, we investigated the statistical measures most distinctive of the various domains and then linked them to our current understandings in so far as possible.